Local increase of the Curie temperature in Mn/Fe implanted Y3Fe5O12 (YIG). (June 2020) - Krastev, P.B.; Gunnlaugsson, H.P.; Nomura, K.; Bharuth-Ram, K.; Qi, B.; Masenda, H.; Mølholt, T.E.; Naidoo, D.; Ólafsson, S.; Martín-Luengo, A. Tarazaga; Unzueta, I.; Johnston, K.; et al.
Abstract: The change in the Curie temperature of single crystalline garnet Y3 Fe5 O12 (YIG) sample due to lattice damage induced by ion implantation has been investigated in 57 Fe emission Mössbauer Spectroscopy (eMS) following implantation of 57 Mn ( T ½  = 1.5 min). The Mössbauer spectra analysis reveal high spin Fe 3+ ions substituted on both the octahedral and the tetrahedral sites. Measurements in the temperature range 298 K–798 K show that average values of the magnetic hyperfine field are decreased by the implantation-induced damage on the local lattice structure of the YIG. The Curie temperature, however, is determined to be 651 ± 5 K, considerably higher than the value of bulk YIG (559 K). This is most likely due to lattice damage-induced changes on the spin configurations of YIG through a Fe A -O-Fe D distortion scheme. Highlights: Implanted Mn atoms enter Fe sites in Y3 Fe5 O12 (YIG). Implantation of YIG increases the local Curie temperature due to implantation damage. Ion implantation is a possible method of tailoring magnetic properties in YIG.